138k views
4 votes
Solve Ax − By = C for x.

x equals the quantity negative B times y plus C all over A
x equals the quantity negative B times y minus C all over A
x equals the quantity B times y minus C all over A
x equals the quantity B times y plus C all over A

2 Answers

4 votes

Answer:

D

Explanation:

User Danivicario
by
5.2k points
3 votes

For this case we have the following equation:


Ax - By = C

From here, we must clear the value of x.

Adding By on both sides:


Ax = By + C

Then, dividing both sides by A we have:


x = \frac {By + C} {A}

Answer:


x = \frac {By + C} {A}

x equals the quantity B times and plus C all over A

User Tekiegirl
by
5.0k points